On Fixed Divisors of Forms in Many Variables, I - Schinzel, A. (MATHEMATICA SCANDINAVICA, 2014)
Let D_d,r be the maximal fixed divisor of a primitive form of degree d in r variables over Z. A formula is given for D_d,2 and estimates for D_d,r for r>2. As a consequence, a question of Nagell raised in 1919 is completely answered.